Formación docente bajo el modelo Pikler-Lóczy en una institución educativa inicial privada en Lima Metropolitana - Caillaux Araujo, Amélie (2020)
This work is based on the evaluation of a team of classroom assistants for children from one to four years old from an initial level educational institution with a pedagogical proposal in-spired by the work of Emmi Pikler. This approach focuses on respect for the child and defends basic quality care. The pedagogical proposal is committed to the need for establishing safe links between children and their caregivers in order to achieve a healthy integral development. A first evaluation of the team confirms the need for intervention by means of training that allows them to implement containment strategies from the Pikler-Lóczy model during the ac-companiment of the integral development of the child, given that only 15% of participants carry out an adequate performance. Consequently, and as a result of the implementation of training workshops and discussion groups with classroom assistants, it has been observed that 85% of the team manages and applies the support strategies proposed by the pedagogical model. Likewise, due to the feats achieved, the need to maintain spaces for reflection and pedagogical updating is considered as a constant in the institution as well as a means that benefits the performance of the professionals.